(untitled) (Development Service Industry Management, 2024)
The article analyzes the state and trends of the Ukrainian labor market in the context of war, highlighting both challenges and adaptive opportunities. The analysis of Ukraine’s labor market during the war reflects profound transformations caused by military actions, economic instability, and mass migration. By the second week of the war, the number of jobs decreased by 55–85%, and 5.3 million Ukrainians had left the country, significantly impacting the labor market. One of the main obstacles for businesses was the labor shortage caused by mobilization and migration. In 2023, 44% of enterprises reported difficulties in workforce supply, while 55.1% noted record challenges in finding qualified employees. The IT sector emerged as the only industry maintaining positive growth, contributing 3.5% of GDP in 2022, made possible through company relocations and the opening of new offices abroad. In 2024, the labor market shows signs of recovery: the number of job vacancies surpassed pre-war levels, with a 77.5% increase in vacancies in front-line regions. However, there remains a significant mismatch between labor demand and supply, particularly at the regional level. The war has brought structural changes to the labor market: demand for remote work has grown (39% increase in vacancies), and the role of women has risen, with 58.8% of new sole proprietors being female. Wage growth has also been observed, with 40.9% of employers increasing salaries in 2024. The article describes government efforts to address the crisis, including the "eRobota" program, which created 55,000 jobs. Despite significant challenges, Ukraine’s labor market demonstrates resilience and adaptability, confirming positive growth trends in 2024, which are critical for the country’s economic recovery. The article examines changes in job demand, particularly in front-line regions, the increase in remote work opportunities, and the growing role of women in entrepreneurship. It also focuses on issues related to wages, employee exemptions from mobilization, and workforce shortages. The labor market is gradually recovering, with the number of vacancies in 2024 exceeding pre-war levels. Automation, workforce retraining, and youth support are identified as key strategies to address the labor shortage. The article emphasizes the importance of developing skills such as multitasking, emotional intelligence, and stress resistance, which are critical for successful employment in 2024–2025.